2000
DOI: 10.1002/(sici)1096-9071(200005)61:1<155::aid-jmv25>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Persistent fetal rubella vaccine virus infection following inadvertent vaccination during early pregnancy

Abstract: Inadvertent immunisation of seronegative women with RA27/3 rubella virus live-attenuated vaccine several weeks before and after conception is described. Whereas in 5 cases the vaccine virus was not transmitted vertically, in 1 case vaccination led to the development of persistent fetal infection with prolonged virus shedding for more than 8 months. Sequence analysis carried out on isolates from amniotic fluid, from cord blood leukocytes as well as from infantile urine confirmed an infection by the vaccine stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A persistent subclinical infection was diagnosed in one case (Hofmann 2000). In none of the children with rubella IgM antibodies was CRS detected.…”
Section: Rubella Vaccinationmentioning
confidence: 89%
“…A persistent subclinical infection was diagnosed in one case (Hofmann 2000). In none of the children with rubella IgM antibodies was CRS detected.…”
Section: Rubella Vaccinationmentioning
confidence: 89%
“…19 There are other similar reports that have shown in a few of susceptible mothers inspite of lack of signs of CRS at birth and longer follow up laboratory signs of rubella infection were evident. 20,21,22 While no case of clinical CRS has ever been reported following rubella vaccination in early pregnancy , in some reports subclinical reinfection with natural rubella virus in pregnant mothers with previously acquired immunity to the disease has caused CRS. 23,24 Of course reinfection is more common amongst people previously immunized via vaccination, not viral infection and who have a serum antibody titer of 1/64 or less.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, twenty-three uncontrolled cohorts [8,[10][11][12][13]22,32, describing pregnancy outcomes after maternal vaccination were retrieved in the literature search. No cases of fetal vaccinia were found among 643 women vaccinated against smallpox [8,58,59], and rates of adverse pregnancy outcomes were within expected limits, except for a high frequency of stillbirth among those vaccinated in the first trimester [59] (Table S7).…”
Section: Uncontrolled Cohortsmentioning
confidence: 99%
“…Two controlled and twelve uncontrolled studies reported on the prevalence of CRS after maternal immunization [10][11][12][13]22,32,[38][39][40][41][42][43]60,61], as shown in Table S8. No cases were detected among 3918 infants, including 2303 born to women susceptible to rubella before vaccination.…”
Section: Uncontrolled Cohortsmentioning
confidence: 99%
See 1 more Smart Citation